Orphan Class A GPCRs Signature Predicts Prognosis and Immune Microenvironment in Gastric Cancer: GPR176 Drives Tumor Progression Through Wnt Signaling and Macrophage Polarization - Jiahui Lin; Lingling Ke; Sha Cheng; Wei Lu; Yanan Hu; Xiyi He; Tingting Luo; Yuting Liu; Canxia Xu; Jian Qi (Mediators of Inflammation)
Conclusion: These findings may provide new insights into the role of orphan class A GPR genes in STAD and identify GPR176 as a new therapeutic target for GC.